EVALUATION OF VITAMIN B12 LEVELS WITH NEUROPATHIC PAIN IN HEMODIALYSIS PATIENTS: A SINGLE CENTER OBSERVATIONAL STUDY - Sri Wijayanti, Ida Ayu; Tresna Erawan, I Gusti Ngurah Agung; Mulyantari, Ni Kadek; Tertia, Clarissa; Widyadharma, I Putu Eka (MNJ (Malang Neurology Journal), 2024)
Background: Uremic syndrome in chronic kidney disease (CKD), particularly in hemodialysis (HD) patients, is a growing global health problem. The majority of patients with this condition experience one or more neurological disorders, such as neuropathic pain. One of the adjuvant therapies in the treatment of neuropathic pain is vitamin B12, which is important for the regeneration and myelination of peripheral nerves and also plays an important role in the restoration of functional nerves. Objective: The aim of this research is to evaluate the role of vitamin B12 in the relief of pain symptoms Method: This research was conducted at General Hospital in Bali use a case-control design and consecutive sampling. This was carried use 21 patients with CKD on regular hemodialysis with neuropathic pain, while 22 patients without neuropathic pain were used as the control group. All patients were tested for serum vitamin B12 levels. Neuropathic pain was assessed using the DN4. Results: The data values of total vitamin B12 levels in blood serum were obtained within a range of 81.72 pmol/L to 2337.5 pmol/L, and a median value of 1306.25 pmol/L. A cut-off value of 1509.375 pmol/L was obtained with 76.2% sensitivity and 59.1% specificity. Furthermore, an odd ratio between low serum vitamin B12 and the incidence of neuropathic pain was also obtained, namely OR= 3.611 (95% CI= 1.012-12.9; p=0.044). Conclusion: It was found that low serum vitamin B12 in CKD patients on hemodialysis increased the risk of experiencing neuropathic pain by 3.611 times compared to those with normal serum vitamin B12.